THE EFFECT OF JOB SATISFACTION AND WORK LIFE BALANCE ON EMPLOYEE ENGAGEMENT AT PT PELAYARAN BAHTERA ADHIGUNA (PT BAg) - Sukmawati, Dina; Agung Priambodo, Ervin; Ishak, Gos (Management and Leadership Study Programme, 2023)
Human Resources is an important element and is the focus of many companies in achieving competitive advantage. Every company expects high engagement from its employees because it greatly influences the company's overall performance and is the key to the company's success and profitability. This study aims to determine how much the factors of job satisfaction and work life balance carried out by PT BAg employees affect employee engagement with the company. The sampling technique used is saturated sampling and the data is processed using a quantitative approach. The population is organic employees and work assignments at PT BAg, totaling 74 employees by distributing a questionnaire of 50 questions. The data analysis method used was multiple linear regression which was analyzed with the SPSS program. The results of this study indicate that job satisfaction has a positive and significant partial effect of 62% on employee engagement, while Work-Life Balance has a partial positive and significant effect of 18% on employee engagement. Simultaneously job satisfaction and work life balance have a positive and significant effect of 74% on employee engagement and the remaining 26% are influenced by other variables not examined in this study.